2018
DOI: 10.1101/430264
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Autoamplification and competition drive symmetry breaking: Initiation of centriole duplication by the PLK4-STIL network

Abstract: Symmetry breaking, a central principle of physics, has been hailed as the driver of selforganization in biological systems in general and biogenesis of cellular organelles in particular, but the molecular mechanisms of symmetry breaking only begin to become understood. Centrioles, the structural cores of centrosomes and cilia, must duplicate every cell cycle to ensure their faithful inheritance through cellular divisions. Work in model organisms identified conserved proteins required for centriole duplication … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 80 publications
0
13
0
Order By: Relevance
“…Polo-like kinase 4 (Plk4) is the master regulator of centriole biogenesis, and it is initially recruited to a ring around the mother centriole, but this ring ultimately resolves into a single focus on the side of the mother, defining the site of daughter centriole assembly (Banterle and Gönczy, 2017;Fırat-Karalar and Stearns, 2014;Leda et al, 2018;Nigg and Holland, 2018;Ohta et al, 2018). Unexpectedly, we found that Plk4 not only determines the position of this site, but also helps to establish the inverse relationship between the rate and period of daughter centriole growth .…”
Section: Discussionmentioning
confidence: 78%
“…Polo-like kinase 4 (Plk4) is the master regulator of centriole biogenesis, and it is initially recruited to a ring around the mother centriole, but this ring ultimately resolves into a single focus on the side of the mother, defining the site of daughter centriole assembly (Banterle and Gönczy, 2017;Fırat-Karalar and Stearns, 2014;Leda et al, 2018;Nigg and Holland, 2018;Ohta et al, 2018). Unexpectedly, we found that Plk4 not only determines the position of this site, but also helps to establish the inverse relationship between the rate and period of daughter centriole growth .…”
Section: Discussionmentioning
confidence: 78%
“…Accumulation of centriole duplication players at the daughter centriole during A-phase, together with the observed association of deuterosomes with the proximal part of the daughter centriole 8 , suggests that, similar to cycling cells, a centriolar wall may serve as a preferential but dispensable nucleation site ensuring a structural patterning 19 and/or facilitating nucleation events 25,26 . Whether the structure of centrioles is affected by the absence of parental centriole needs further investigation 19 .…”
Section: Discussionmentioning
confidence: 99%
“…4c and Supplementary Videos 4,5). This non-homogenous distribution may arise as a result of a symmetry-breaking reaction that creates a non-uniform distribution of PLK4, similar to what occurs in cycling cells 27 . Alternatively, procentrioles may detach from the walls of the parent centrioles, which could explain their presence in close proximity to the parent centrioles (Fig.…”
Section: Fig 3 | Live Imaging Of Differentiating Deup1mentioning
confidence: 92%